2019
DOI: 10.1177/0743558418822332
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Feasibility of Measuring Recovery in Adolescent Participants of an Alternative Peer Group: Lessons Learned and Next Steps

Abstract: The aim of this article is to report lessons learned from feasibility challenges faced in a mixed-methods study designed to test the feasibility of measuring recovery in participants of an Alternative Peer Group (APG). The APG integrates pro-recovery peers and social activities into clinical practice to engage adolescents in recovery. Though well established, APGs have never been tested. This study was one phase in a line of research that aims to develop an APG evidence base. The study used a mixed-methods des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…In another study, adolescents who were actively or recently involved in an APG reported mixed perceptions of the 12 steps. 48,59 Consistent with prior qualitative work, 56,57 low problem recognition, poor motivation for treatment, and stereotypes about 12-step groups were common negative initial perceptions. 48 However, as peers advocated for the benefits and the participants tried working the steps, these initial negative impressions became more positive.…”
Section: Adolescents' Perceptions Of the 12 Stepssupporting
confidence: 60%
“…In another study, adolescents who were actively or recently involved in an APG reported mixed perceptions of the 12 steps. 48,59 Consistent with prior qualitative work, 56,57 low problem recognition, poor motivation for treatment, and stereotypes about 12-step groups were common negative initial perceptions. 48 However, as peers advocated for the benefits and the participants tried working the steps, these initial negative impressions became more positive.…”
Section: Adolescents' Perceptions Of the 12 Stepssupporting
confidence: 60%
“…26 The findings of this study concur with the Adolescent Recovery Model (Figure 3). 32 This model depicts adolescent recovery as a protracted process consisting of four distinct but iterative stages that may or may not involve relapse. Elements such as sober fun, relationships with recovering role models, and time emerged as critical to the initiation, progression, and maintenance of recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Elements such as sober fun, relationships with recovering role models, and time emerged as critical to the initiation, progression, and maintenance of recovery. 3,32 A mainstay of SUD treatment across all age ranges involves helping affected individuals resolve their ambivalence and thus, increase their motivation to pursue recovery. 36 It is not surprising that the advantages and disadvantages of APG elements reported by participants of this study seemed to emerge as a continuum that changed over time as their ambivalence resolved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to some ambiguity about how best to separate the RC domains to understand them as entities in the real world and as things that can be reliably measured, we lack a common understanding of the key factors within a domain that best indicate the presence of RC [20,[32][33][34][35][36] and whether/how these vary by population. For example, although employment is one component of human RC for adults [36,37], it is likely not yet important for youth populations in recovery for whom school engagement would be more relevant.…”
Section: Conceptual Developmentmentioning
confidence: 99%